Earning response coefficients of firms in merger and acquisition. - Cheng, Fan Fah; Md Nasir, Annuar; Lim, Voon Lee (Universiti Putra Malaysia Press, 2012)
A large body of studies has done to examine the fundamental relationship between accounting variables and firm valuation using earnings response coefficients. They further demonstrate that the earnings have valuation and information content. In fact, when investors weight current-period earnings heavily, the stock price response to earnings is much greater and more persistent. However, in terms of acquisition events, whether earnings are informative as measured by the magnitude of the related stock price response conditional on unexpected earnings is a question because the only few research conducted earlier are more concentrate on the merger event. Therefore, this study is important in order to verify or reject the characteristics of return-earnings relationship identified in samples of acquiring and acquired firm in the Malaysia market. The results displayed in the study reveal that the stock prices change in a statistically significant manner in response to earnings increases and decreases is quite evident only on the target firms and not on the acquiring firms. The poor price-to-earnings association before and after the announcement dates on the acquiring firms is due to overestimation of the public on the future economic value that can gain after the corporate merger/acquisition. The effect is also strong over in the short window interval and not the long window interval.